Addition of bevacizumab to chemotherapy in advanced non-small cell lung cancer: a systematic review and meta-analysis. - André Bacellar Costa Lima; Ligia T Macedo; André Deeke Sasse (PLoS ONE)
Introduction Recently, studies have demonstrated that the addition of bevacizumab to chemotherapy could be associated with better outcomes in patients with advanced non-small cell lung cancer (NSCLC). However, the benefit seems to be dependent on the drugs used in the chemotherapy regimens. This systematic review evaluated the strength of data on efficacy of the addition of bevacizumab to chemotherapy in advanced NSCLC. Methods PubMed, EMBASE, and Cochrane databases were searched. Eligible studies were randomized clinical trials (RCTs) that evaluated chemotherapy with or without bevacizumab in patients with advanced NSCLC. The outcomes included overall survival (OS), progression-free survival (PFS), response rate (RR), toxicities and treatment related mortality. Hazard ratios (HR) and odds ratios (OR) were used for the meta-analysis and were expressed with 95% confidence intervals (CI). Results We included results reported from five RCTs, with a total of 2,252 patients included in the primary analysis, all of them using platinum-based chemotherapy regimens. Compared to chemotherapy alone, the addition of bevacizumab to chemotherapy resulted in a significant longer OS (HR 0.89; 95% CI 0.79 to 0.99; p = 0.04), longer PFS (HR 0.73; 95% CI 0.66 to 0.82; p<0.00001) and higher response rates (OR 2.34; 95% CI 1.89 to 2.89; p<0.00001). We found no heterogeneity between trials, in all comparisons. There was a slight increase in toxicities in bevacizumab group, as well as an increased rate of treatment-related mortality. Conclusions The addition of bevacizumab to chemotherapy in patients with advanced NSCLC prolongs OS, PFS and RR. Considering the toxicities added, and the small absolute benefits found, bevacizumab plus platinum-based chemotherapy can be considered an option in selected patients with advanced NSCLC. However, risks and benefits should be discussed with patients before decision making.